TACTICS AND STRATEGY OF ETIOTROPIC TREATMENT OF ARVI AND INFLUENZA IN CHILDREN - L.N. Mazankova; A.A. Cheburkin ("Paediatrician" Publishers LLC, 2009)
Administration of etiotropic medications, blocking a penetration of virus into the cell and/or suppress its replication, is advisable additionally to the vaccination as main strategy against acute respiratory viral infection (ARVI) and influenza in children. As etiological diagnostics of ARVI and influenza demands time and sometimes it can't be provided, the antiviral treatment may be started if there are indications for its administration without identification of pathogen, following medical history and clinical picture of the disease. One of the main prevalent medications with etiotropic activity is rimantadine. New polymeric medication for children based on rimantadine is Orvirem. It is complex of rimantadine, fixed to sodium alginate, amplifying antitoxic activity of a medication and providing its improved tolerance. Such pharmacological formula provides gradual entrance of rimantadine into the blood, its prolonged circulation in organism, constant concentration in blood and decreasing of toxic effect of the drug. Due to these properties, the medication can be used for the prophylaxis and treatment of influenza and ARVI in children older than 1 year old. The medication combines as direct antiviral activity, as immunomodulating effect, resulting in restoration of cell immunity. Clinical studies showed drug's effectiveness and safety in patients with influenza type A and B, with adenoviral, respiratory-syncytial viral and mycoplasmal infections. Prophylactic effect of the medication in inevitable contact with patients with ARVI, including children's group was also proved.Key words: children, viral infections, rimantadine, treatment.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):126-130)